Analysis of Public Trust toward Cleanliness, Health, Safety, and Environmental Sustainability (CHSE) Certification Policy in Surabaya City - Izzah Illiyyina; Fitra Adinia Rahmi; Romy Hafizh Lesmana; Arimurti Kriswibowo (Universitas Muhammadiyah Malang, 2021)
The era of adapting to new habits as a trigger for economic development is expected to generate a sense of public trust to return to travel in the Pandemic Era. This policy also aims to build entrepreneurs' confidence in the tourism sector to survive in the era of adaptation to new habits, given that the (Cleanliness, Health, Safety, and Environmental Sustainability) CHSE certification policy is open to all tourism businesses in Indonesia. The Interesting matter in this research was that researchers could find benchmarks for the success of CHSE policies in Surabaya City through the level of public trust in tourism business actors who have been CHSE certified by the Ministry of Tourism and Creative Economy. The objective of this scientific research is relevant and actual nowadays because it can determine the level of public confidence in the CHSE certification policy in the city of Surabaya. The method used in this research was quantitative with 100 samples. This study shows that the CHSE policy is positively appreciated by the people of the City of Surabaya because it is considered to guarantee public safety in the new normal era. The implementation of the CHSE Certification makes business actors consistent in implementing health protocols so that people feel protected from Covid-19. In the future, this policy still needs to be maintained with strict supervision and enforcement of violations and expanded socialization to reach all tourism actors.